Interpersonal Metadiscourse Markers as Persuasive Strategies in Oral Business Presentation - Kuswoyo, Heri; Siregar, Rani Andini (Bina Nusantara University, 2019)
This research was conducted to examine the use of interpersonal metadiscourse markers (IMDMs) in Steve Jobs’ oral business presentation using Hyland’s model. It further aimed to investigate the interpersonal metadiscourse categories and subcategories applied and most predominantly occurring in the type of oral business presentation. A descriptive qualitative method was employed in this research. One and a half-hour of Steve Jobs’ keynotes at annual Macworld tradeshow on January 9th, 2007 were collected and analyzed. The results reveal that interactional subcategory; engagement markers are mostly used by Steve Jobs. Meanwhile, in interactive subcategory transition markers are dominantly used. It indicates that by using interpersonal metadiscourse markers, Steve Jobs expresses his idea, supports his argument, and convinces the audiences by establishing a relationship with them. This research also argues that metadiscourse theory facilitates an involvement between the speaker and the listener and provides a way for mutual comprehension. Thus, the findings have a pivotal implication on how IMDMs might improve the field related to communication skills in professional life or business.